The domestic wastewater treatment capacity of Spirulina platensis SP4 and the application of the treated wastewater in stimulating rice germination - Thi Kieu Oanh, Nguyen; Thi Thuy, Duong; Thi Oanh, Doan; Thi Nguyet, Vu; Van Nam, Nguyen (Vietnam Journal of Biotechnology, 2022)
Many scientists are interested in microalgae and cyanobacteria because of their richness in high-value bioactive metabolites (proteins, lipids, vitamins, plant growth regulators, and others). Microalgae and cyanobacteria can be used to produce valuable commodities such as dietary supplements, biofuel, animal feed, and agricultural fertilizer, etc. To improve the economic feasibility of the cyanobacterial product recovery process, it is possible to utilize domestic wastewater as a source of nutrients for their growth. This research focuses on assessing the ability of domestic wastewater treatment and treated domestic wastewater utilization to stimulate BC15 rice-grain sprouting by cyanobacteria Spirulina platensis SP4. Research results showed that S. platensis SP4 grown best in domestic wastewater at the initial density of 0.3 and the wastewater concentration of 100%. The incubation of S. platensis was performed in the laboratory under the condition of 16.8 g/L NaHCO3; aeration during 8 h/day; light: dark cycle of 8:16; light intensity of 5000 lux. Under these conditions S. platensis SP4 could treat N-NH4+, T-N, P-PO43-, T-P and COD well with the treatment efficiency of 96.37, 49.71, 67.05, 65.88 and 95.53%, respectively. The addition of treated domestic wastewater by S. platensis SP4 to BC15 rice grains stimulated the grouting by 99.54 ± 1.25%, which was 1.54 times higher than using the tap water and gave a germination efficiency equivalent to that of the experiments with adding cyanobacteria in standard medium with or without L-tryptophan addition for 48 h. The obtained research results have elucidated the feasibility of employing cyanobacteria in residential wastewater treatment as well as the reuse of treated wastewater for plant development.